2020
DOI: 10.1016/j.pdpdt.2020.101675
|View full text |Cite
|
Sign up to set email alerts
|

Can ethanol affect the cell structure? A dynamic molecular and Raman spectroscopy study

Abstract: The role that tobacco consumption plays in the etiology of oral cancer carcinogenesis, and of alcohol consumption acting as a co-factor, have been well established. However, in recent years, the contribution of alcohol consumption alone to oral cancer has been proposed. In fact, a high percentage of patients who develop oral cancer have both habits (tobacco and alcohol consumption), and other small patient groups only consume alcohol or do not have any other identifiable bad habits. In the present study, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Indeed, previous research indicated that ethanol affects cell membrane fluidity and increased permeability. 26 , 80 , 81 Similarly, ethanol is known to cause increased membrane permeability as well as changes in membrane composition in S. cerevisiae . 82 , 83 It is currently unclear if and how ethanol-associated membrane damage could initiate carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous research indicated that ethanol affects cell membrane fluidity and increased permeability. 26 , 80 , 81 Similarly, ethanol is known to cause increased membrane permeability as well as changes in membrane composition in S. cerevisiae . 82 , 83 It is currently unclear if and how ethanol-associated membrane damage could initiate carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer is the eighth most common form of cancer worldwide. The increased risk factors for developing esophageal cancer include smoking ( 3 , 4 ), the consumption of high-percentage alcohol ( 5 ), obesity ( 6 ), long-term inflammation of the esophagus mucosa ( 7 ), achalasia ( 8 ), atrophic inflammation of the tongue and esophagus ( 9 ), Barrett’s esophagus ( 10 , 11 ), burns of the esophagus with chemicals ( 12 ), occupational exposure to vulcanization products ( 13 ), asbestos and metal dust ( 14 ), dietary factors ( 11 ), vitamin deficiencies ( 15 ) and trace elements, and frequent consumption of hot and pickled foods ( 16 ).…”
Section: Esophageal Cancermentioning
confidence: 99%
“…One of these applications is oral cancer diagnosis. During the progression of cancer, biochemical changes occur within the cancer cells [1], altering the levels of nucleic acids, lipids and carbohydrates that can serve as biomarkers for monitoring diseases [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For all the aforementioned reasons, a non-invasive, real-time point-of-care method to detect and accurately diagnose cancer and premalignancies at early stages could benefit patients as well as decrease the risk of oral cancer incidence and mortality. One of the most cost-effective methods to diagnose cancer is the optical biopsy [1,3,[10][11][12][13][14][15][16][17][18]. The term optical biopsy is widely used in optical spectroscopy [6,14,[19][20][21][22][23][24], which assists in the diagnostic process and analyzes optical properties [19,[25][26][27] associated with tissue biochemistry [3][4][5][6][7][8][9]14,16,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%